2018
DOI: 10.29333/djfm/5829
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Financial Leverage Ratio before and after the Use of Off-Balance Sheet Financing in Firms Listed in the Tehran Stock Exchange

Abstract: The aim of this study was to compare the proportion of financial leverage in companies before and after the use of off-balance sheet financing in firms listed in the Tehran Stock Exchange. The research method was causal-comparative descriptive. The population was all the accepted companies in Tehran Stock Exchange (cars and car fragments, petrochemicals, petroleum products, cement, pharmaceutical, home and sugar appliances) between years of 2010 and 2014 that 87 companies were selected at random. Data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…Hurt, Moss, Bradley, Larson, and Richard Lovelace emphasize that The students aren't feel uncomfortable in the communication with their lecturers on Facebook which teachers produce new profiles to move with their students United Nations agency lack personal info by showing solely a profile picture [10]. four-hundredth of lecturers connect with their students through Facebook, 16 PF have used it within the past, and forty first have not communicated with their students via Facebook, ninety one of scholars have not used Facebook to speak with their teachers; sixty eight didn't visit the profile of their faculty member on Facebook, and forty first indicated that they might not need their lecturers to speak with them through Facebook [11]. Erjavec noted that the majority students didn't communicate with their lecturers on social networks [12].…”
Section: Resultsmentioning
confidence: 99%
“…Hurt, Moss, Bradley, Larson, and Richard Lovelace emphasize that The students aren't feel uncomfortable in the communication with their lecturers on Facebook which teachers produce new profiles to move with their students United Nations agency lack personal info by showing solely a profile picture [10]. four-hundredth of lecturers connect with their students through Facebook, 16 PF have used it within the past, and forty first have not communicated with their students via Facebook, ninety one of scholars have not used Facebook to speak with their teachers; sixty eight didn't visit the profile of their faculty member on Facebook, and forty first indicated that they might not need their lecturers to speak with them through Facebook [11]. Erjavec noted that the majority students didn't communicate with their lecturers on social networks [12].…”
Section: Resultsmentioning
confidence: 99%
“…In addition these ideologemes are distributed into groups in accordance with O.S.Issers's classification [Issers 2008: Mardani, & Fallah 2018. She considers speech action impact as one of operations on semantic networks characterized by discontinuity (the most frequent scheme in the selected contexts «A is not B») and by establishment of new associative dependencies (the most frequent schemes in the selected contexts «A is B» and «A has a sign of B»).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the high potential, it still does not play a significant role in the country's economy (The Art Market 2019). Serious changes are taking place in financial markets; frequent global financial fluctuations in art markets contribute to non-typical players participating who seek to preserve their capital through investments in the art industry (Korhonen & Lyakin, 2017;Vodopianova et al, 2018;Mardani & Fallah, 2018). To some extent, this situation correlates with the efficiency of the banking sectors in various countries (Balcerzak et al, 2017).…”
Section: Theoretical Basementioning
confidence: 99%